2003
DOI: 10.1002/chir.10229
|View full text |Cite
|
Sign up to set email alerts
|

Chiral aspects of metabolism of antiinflammatory drug flobufen in human hepatocytes

Abstract: The metabolism of the nonsteroidal antiinflammatory drug flobufen, 4-(2',4'-difluorobiphenyl-4-yl)-2-methyl-4-oxobutanoic acid, was studied in primary cultures of human hepatocytes prepared by two-step collagenase perfusion of livers from four donors. Racemic flobufen or its individual enantiomers, R-(+)- and S-(-)-flobufen were used as substrates. Aliquots of culture medium were collected during 24-h incubation. The time-dependent disappearance of flobufen enantiomers and the formation of metabolites (stereoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The stereochemistry of ketone reduction has been reported for a number of xenobiotics (Asami et al, 1996;Benedetti et al, 1991Benedetti et al, , 1993Breyer-Pfaff and Nill, 1995;Dow and Berg, 1995;Eyles and Pond, 1992;Hermans and Thijssen, 1989;Kume et al, 2000;Lawrence et al, 1990;McMahon et al, 1965;Nagata et al, 1992;Nicklasson et al, 2002;Rush et al, 1990;Skálová et al, 2003;Takasaki and Tanaka, 1992;Vickers et al, 1993;Volosov et al, 1999;Weil et al, 1989;Wsól et al, 1998a). However, the absolute configuration has not been determined in all cases.…”
Section: Human Carbonyl Reduction Pathways 339mentioning
confidence: 91%
“…The stereochemistry of ketone reduction has been reported for a number of xenobiotics (Asami et al, 1996;Benedetti et al, 1991Benedetti et al, , 1993Breyer-Pfaff and Nill, 1995;Dow and Berg, 1995;Eyles and Pond, 1992;Hermans and Thijssen, 1989;Kume et al, 2000;Lawrence et al, 1990;McMahon et al, 1965;Nagata et al, 1992;Nicklasson et al, 2002;Rush et al, 1990;Skálová et al, 2003;Takasaki and Tanaka, 1992;Vickers et al, 1993;Volosov et al, 1999;Weil et al, 1989;Wsól et al, 1998a). However, the absolute configuration has not been determined in all cases.…”
Section: Human Carbonyl Reduction Pathways 339mentioning
confidence: 91%
“…Knadler and Hall [20] described the racemization and hydrolysis of CoA thioesters of (R)-ibuprofen and (R)-fenoprofen with rat liver microsomal and mitochondrial fractions, which supported the findings of Nakamura et al [36]. Skalova et al [37] reported chiral inversion of R-(+)-flobufen and (2S;4S)-dihydroflobufen (DHF) in human hepatocytes. The authors also reported the unidirectional chiral inversion of the enantiomers of dihydroflobufen (DHF) as (2S;4S)-DHF to (2R;4S)-DHF and from (2R;4R)-DHF to (2S;4R)-DHF in hepatocyte cultures.…”
Section: In Vitro Racemizationmentioning
confidence: 58%
“…31 Knadler and Hall 32 reported the racemization and hydrolysis of CoA thioesters of (R)-ibuprofen and (R)-fenoprofen with rat liver microsomal and mitochondrial fraction, which supported the findings of Nakamura et al 33 in 1981. Skalova et al 34 reported chiral inversion of R-(þ)-flobufen and (2S;4S)-dihydroflobufen (DHF) in human hepatocytes. The authors also reported the unidirectional chiral inversion of the enantiomers of dihydroflobufen (DHF) as (2S;4S)-DHF to (2R;4S)-DHF and from (2R;4R)-DHF to (2S;4R)-DHF in hepatocyte cultures.…”
Section: In Vitro Racemizationmentioning
confidence: 99%